2021
DOI: 10.3389/fpsyt.2021.549810
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Reliable Rat Model of Autism

Abstract: Background: Autism spectrum disorders (ASD) is a complex neurodevelopmental disorder that lacks an ideal animal model to recapitulate the disease state of ASD. Previous studies have reported that transplanting gut microbiota of ASD patients into pregnant mice is sufficient to promote the changes of autism-like behavior in offspring. This study aims to explore whether fecal microbiota transplantation (FMT) can be used as a new method to establish the ASD animal model.Methods: We transplanted the fecal sample ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 61 publications
(81 reference statements)
1
24
0
Order By: Relevance
“…In the peripheral system, previous studies have found elevated 5-HT levels in serum, plasma or gastrointestinal tract of VPA-treated rodents, which support the general hyperserotonemia theory of ASD etiology [14,[83][84][85]. However, other studies have reported the reduction in 5-HT-positive cells in the ileum, 5-HT levels and its precursors (tryptophan and 5-HTP), and metabolites (5-HIAA) in both the peripheral system and brain [22,[86][87][88][89].…”
Section: Abnormalities Of Serotonergic Systems In Vpa-induced Asd Modelsmentioning
confidence: 74%
“…In the peripheral system, previous studies have found elevated 5-HT levels in serum, plasma or gastrointestinal tract of VPA-treated rodents, which support the general hyperserotonemia theory of ASD etiology [14,[83][84][85]. However, other studies have reported the reduction in 5-HT-positive cells in the ileum, 5-HT levels and its precursors (tryptophan and 5-HTP), and metabolites (5-HIAA) in both the peripheral system and brain [22,[86][87][88][89].…”
Section: Abnormalities Of Serotonergic Systems In Vpa-induced Asd Modelsmentioning
confidence: 74%
“…Various technics/chemicals such as folic acid, thalidomide, valproic acid, propionic acid, and D2 dopamine receptor heterozygous knockout model are used to experimentally induce autistic features in rodents [ 53 , 54 , 55 , 56 , 57 , 58 ]. Numerous studies have proven that the VPA model can be used as an essential tool to examine the underlying mechanism of ASD [ 59 ]. However, this model also has some limitations [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the transplantation of feces from children with autism induces autism-like behaviors as well as altered tryptophan and serotonin metabolism in germ-free recipient mice [ 103 ]. Another study reports that an autism rat model, transplantation with fecal samples from children with autism results in a decrease in the serum levels of GABA and norepinephrine, an increase in the serum level of serotonin, and increases in the abundance of Lactobacillus and Collinsella [ 104 ]. These results suggest that a typical gut microbial composition from patients with a certain disorder can trigger a disease symptom that is usually accompanied by alterations in neurotransmitter levels.…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%